La formación del profesor de historia y geografía. Clío, Comenius o la actualidad de un debate (Educational Perspectives Magazine (REPED), 2022)
The formation of the professor of history and geography has been characterized by a historical tensión between the training focused on the discipline and one that emphasizes the didactic. This was influenced by the contextual framework in which this tensión is particularly exacerbated during the processes of educational reform as the one currently living in our country. For all these reasons, it is required to explorea new profile that defines the type, character training and guidance of Professor of History and Geography, resignifying the space of the professional practices as the core of the training.